A Study on The Minimum Exposure Dose For Image Formation In X-Ray Imaging of Extremity - Yu, Sinyoung (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Excellent performance of the digital detector can generate medical images at a lower dose. However, if a certain level of dose exposure of the sensor detector can generate an image to recognize it. In this study, the exposure conditions of the forearm, femur, and ankle joint tests currently used in clinical trials were tested with lower doses. The resolution pattern was analyzed using the Image J program, and the results were obtained by analyzing the Interactive 3D Surface Plot. In addition, by measuring the surface dose and absorbed dose, the digital detector finds the minimum conditions to make an image, and also checks the effect of dose reduction. The image of the obtained resolution pattern was analyzed by Plot profile using Image J program. It was confirmed that the gray value width decreased at the same pixel distance as the exposure conditions decreased. Even if the exposure conditions were lowered from step 1 to step 4, which is the standard condition of the forearm test, the resolution showed no difference at 1.4 Lp/mm. In the Interactive 3D Surface Plot, as the range of the gray scale lowered the exposure condition, the shape of the surface contours gradually became blurred and the contrast of black and white shades decreased. The resolution from step 1 to step 3, which is the standard condition of the femur bone test, was 1.2 Lp/mm, indicating no difference. Even if the exposure conditions were lowered from step 1 to step 4, which is the standard condition for ankle examination, the resolution showed no difference at 1.4 Lp/mm. It is thought that it is necessary to accumulate a lot of data by further subdividing the stage of exposure conditions according to the thickness in more areas.